Transitioning to a national health system in Cyprus: a stakeholder analysis of pharmaceutical policy reform - Olivier J Woutersa; Panos G Kanavosa (The World Health Organization, 2015)
Abstract Objective To review the pharmaceutical sector in Cyprus in terms of the availability and affordability of medicines and to explore pharmaceutical policy options for the national health system finance reform expected to be introduced in 2016. Methods We conducted semi-structured interviews in April 2014 with senior representatives from seven key national organizations involved in pharmaceutical care. The captured data were coded and analysed using the predetermined themes of pricing, reimbursement, prescribing, dispensing and cost sharing. We also examined secondary data provided by the Cypriot Ministry of Health; these data included the prices and volumes of prescription medicines in 2013. Findings We identified several key issues, including high medicine prices, underuse of generic medicines and high out-of-pocket drug spending. Most stakeholders recommended that the national government review existing pricing policies to ensure medicines within the forthcoming national health system are affordable and available, introduce a national reimbursement system and incentivize the prescribing and dispensing of generic medicines. There were disagreements over how to (i) allocate responsibilities to governmental agencies in the national health system, (ii) reconcile differences in opinion between stakeholders and (iii) raise awareness among patients, physicians and pharmacists about the benefits of greater generic drug use. Conclusion In Cyprus, if the national health system is going to provide universal health coverage in a sustainable fashion, then the national government must address the current issues in the pharmaceutical sector. Importantly, the country will need to increase the market share of generic medicines to contain drug spending.